Civic participation digitalisation: limitations in the digital divides ﬁeld - M. A. Gruzdeva (Цифровая социология, 2022)
In Russian public discourse, digitalisation is recognised as a new global trend, which creates an environment with extensive communication possibilities and leads to the civic participation traditional practices reformatting to online. In this regard, it is relevant to study the opportunities, risks and necessary conditions for these transformations. The aim of the article is to identify the civic participation digitalisation limitations of the population, lying in the digital differences ﬁeld. Settlement, age, gender, educational and income factors of Internet accessibility, its use purposes and digital skills availability for Russian regions, including the Vologda Region as a typical region are considered. To solve the research problems, sociological methods, secondary data analysis, the system-structural and cross-tabulation analysis method were used. The results of the study conducted have made it possible to identify characteristics according to which certain population groups have a high, medium or low potential for civil society digital inclusion in terms of technical accessibility, knowledge and the Internet experience and digital services. The online citizenship format is most likely to be attractive to young and middle-aged people, working and living in cities, with secondary vocational or higher education. At the research time, no signiﬁcant gender impact and self-reported income on the digital divides was identiﬁed. However, current trends consideration in digitalisation and prolonging the older people active lives makes it possible to argue that potential participants groups in civic participation in an online format will expand in the future. The study results can be considered when planning the civil society development, taking into account current trends, developing tools to motivate different socio-demographic population groups to civic engagement online.